Construction of Lyapunov functions for continuous and discontinuous homogeneous systems - Sánchez Ramírez, Tonámetl (My University, 2016)
Ingeniería de Control Control automático Funciones de Lypunov
Keywords: Ingeniería de Control Control automático Funciones de Lypunov